Effect of Temperature on the Formation of Cu(II) TernaryChelates of Substituted Phenylhydrazonopropanoic acid - Kodanda Ramaiah, E.; Ram, Kashi (Asian Journal of Chemistry, 2010)
Formation constants have been measured for the mixed ligand complexes Cu(II)-A-L or Cu(II)-L´-A, where A = 2-(phenylhydrazono)- propanoic acid, 2-(p-nitro-phenylhydrazono)-propanoic acid, 2-(p-tolylhydrazono)-propanoic acid; L = catechol, ethylenediamine, proline, hydroxyproline, β-alanine, glycine and L´ = 1,10- phenanthroline, salicylic acid at 20º, 30º, 40º and 50ºC in 40% (v/v) ethanol-water medium at 0.10 M (KNO3) ionic strength. Thermodynamic parameters for the above systems have been evaluated and discussed in terms of the basicity of the ligands, electrostatic interaction, metal-ligand π-interaction, denticity and statistical aspects.